Efectiveness of Block System Learning on Grade X Student of Business Management and Office Services Expertise Program - Sukamto, Dinda Dwi Lukita; Wulandari, Siti Sri; Sudarwanto, Tri; Soesatyo, Yoyok; Susanto, Bambang Adi (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: One of the important elements in the implementation of education is an effort to improve the quality of learning. Until now, the implementation of learning in vocational schools still follows a non-block system. This condition results in the practice carried out by students not achieving optimal completion, so that the required standard competencies are not met. One solution is to implement a block learning system including the effectiveness of time, tools, and location. This type of research is quantitative with a population of class X students of the office management and business service expertise program at SMKS YPM 3 Taman. The results of the study found that regarding learning using the block system, many students stated that this system was not boring. In our study on the implementation of the block system, they argued that the block system helps students focus more on learning because it uses a longer time. Methodology/Approach: This study adopts a quantitative approach Findings: In our study on the implementation of the block system, many students stated that this system is not boring. They argued that the block system helps students focus more on learning because it uses a longer time. Research limitations/implications: The limitation of this study is that the population focus was only taken from 1 school. Practical implications: For further research, it is hoped that several populations from various new schools that are implementing the block system can be used. Originality/value: Original Paper type: Research paper